Three-Dimensional Reconstruction and Numerical Simulation Analysis of Acid-Corroded Sandstone Based on CT - Zizhen Miao; Shuguang Li; Jiangsheng Xie; Runke Huo; Fan Ding; Hongtao Zhu; Xingzhi Yang; Xiaoke Li (Shock and Vibration)
Due to its unique technological characteristics, coal mining and production often encounter an acid corrosion environment caused by acid gases. Acid erosion and a series of chemical reactions caused by it often led to the deterioration of coal, rock, support structure, etc. and induced serious safety accidents. To further explore the macro-mesoscopic damage evolution law and failure mechanisms of rock masses under corrosion conditions through numerical simulation, a zonal refined numerical model that can reflect the acid corrosion characteristics of sandstone is established based on CT and digital image processing (DIP). The uniaxial compression test of corroded sandstone is simulated by ABAQUS software. Comparing the numerical simulation results with the physical experiment results, we found that the three-dimensional finite element model based on CT scanning technology can genuinely reflect sandstone’s corrosion characteristic. The numerical simulation results of the stress-strain curve and macroscopic failure mode of the acid-corroded sandstone are in good agreement with the experimental results, which provides a useful method for further studying the damage evolution mechanism of the acid-corroded rock mass. Furthermore, the deformation and damage evolution law of the corroded sandstone under uniaxial compression is qualitatively analyzed based on the numerical simulation. The results show that the rock sample’s axial displacement decreases gradually from top to bottom under the axial load, and the vertical variation is relatively uniform. In contrast, the rock sample’s removal gradually increases with the increase of axial pressure, and the growth presents a certain degree of nonuniformity in the vertical. The acid-etched rock sample’s damage starts from both the end and the middle; it first appears in the corroded area. Moreover, with the displacement load increase, it gradually develops and is merged in the middle of the rock sample and forms macroscopic damage.